Clinical Correlations of Lipid Profiles with the Age and Gender in the Coronary Artery Disease Patients: A Study of 3878 CAD Patients from India - Mir, Rashid; Elfaki, Imadeldin; Frah, Ehab A.M.; Alzahrani, Khalid J.; Mir, Mohammad M.; Banu, Shaheena (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Cardiovascular diseases (CVDs) are crucial cause of death and hospitalization all over the world including India. The CVDs including the coronary artery disease (CAD) are developed by the interaction of genetic and environmental factors. Hyperlipidemia is a traditional risk factor for CVD. Aim: The aim of this study was to study the clinical correlations of lipid profiles with the age and gender in the Coronary Artery Disease Patients: Methods: In this study, we have investigated the effect of age and sex on in lipid profile in 3878 (1171 females and 2707 males) CAD patients from India. Results: The plasma TG was higher in males than in females regardless of the age. Results showed that CAD female patients had significantly increased HDL-C than their aged matched males. Moreover, the plasma TC and LDL-C were significantly higher in males than females until age 40 years. Then after the age of 40 years, TC and LDL-C become significantly higher in females than in males. In addition, we found that more than 85% of CAD cases were <55 years old, and about 30% of CAD cases had normal lipid profile. Conclusion: We conclude that elderly females are at a greater risk for CAD than males. Moreover, there were no significant differences in CVDs causes between nonelderly and elderly females. In addition, a higher percentage of cases were premature CAD, and 30% of CAD may be caused by loci that are not related to lipid metabolism.
Keywords: cardiovascular disease